eIF2α confers cellular tolerance to S. aureus α-toxin - von Hoven, Gisela; Neukirch, Claudia; Füser, Sabine; Bidna Petrivna, Maria; Meyenburg, Martina; Rivas, Amable J.; Ryazanov, Alexey; Kaufman, Randal J.; Aroian, Raffi V.; Husmann, Matthias (Frontiers in Immunology, 2015)
We report on the role of conserved stress–response pathways for cellular tolerance to a pore forming toxin. First, we observed that small molecular weight inhibitors including of eIF2α-phosphatase, jun-N-terminal kinase (JNK), and PI3-kinase sensitized normal mouse embryonal fibroblasts (MEFs) to the small pore forming S. aureus α-toxin. Sensitization depended on expression of mADAM10, the murine ortholog of a proposed high-affinity receptor for α-toxin in human cells. Similarly, eIF2αS51A/S51A MEFs, which harbor an Ala knock-in mutation at the regulated Ser51 phosphorylation site of eukaryotic translation initiation factor 2α, were hyper-sensitive to α-toxin. Inhibition of translation with cycloheximide did not mimic the tolerogenic effect of eIF2α-phosphorylation. Notably, eIF2α-dependent tolerance of MEFs was toxin-selective, as wild-type MEFs and eIF2αS51A/S51A MEFs exhibited virtually equal sensitivity to Vibrio cholerae cytolysin. Binding of S. aureus α-toxin to eIF2αS51A/S51A MEFs and toxicity in these cells were enhanced as compared to wild-type cells. This led to the unexpected finding that the mutant cells carried more ADAM10. Because basal phosphorylation of eIF2α in MEFs required amino acid deprivation-activated eIF2α-kinase 4/GCN2, the data reveal that basal activity of this kinase mediates tolerance of MEFs to α-toxin. Further, they suggest that modulation of ADAM10 is involved. During infection, bacterial growth may cause nutrient shortage in tissues, which might activate this response. Tolerance to α-toxin was robust in macrophages and did not depend on GCN2. However, JNKs appeared to play a role, suggesting differential cell type and toxin selectivity of tolerogenic stress responses. Understanding their function or failure will be important to comprehend anti-bacterial immune responses.